2013
DOI: 10.3748/wjg.v19.i27.4289
|View full text |Cite
|
Sign up to set email alerts
|

miR-20b, miR-98, miR-125b-1*, and let-7e* as new potential diagnostic biomarkers in ulcerative colitis

Abstract: Author contributions: Coskun M and Bjerrum JT performed the experiments and data analysis, wrote the manuscript, and wrote the final revision of the article; Troelsen JT provided with analytical tools, intellectual input and advice; Olsen J provided with reagents and human tissue; Seidelin JB and Nielsen OH contributed to the conceptual design, drafting of the manuscript and revising it critically for important intellectual content; all authors approved the final submitted manuscript. Abstract AIM: To use micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 74 publications
(86 reference statements)
2
60
0
Order By: Relevance
“…MVDA effectively addresses complex information using advanced statistical algorithms and has been applied in the biopharmaceutical industry, including fermentation critical process data analysis, NIR spectral data analysis, and biomarker identification [40, 41]. We used MVDA to analyze the RPKM data to identify “biomarkers” of different DO conditions.…”
Section: Resultsmentioning
confidence: 99%
“…MVDA effectively addresses complex information using advanced statistical algorithms and has been applied in the biopharmaceutical industry, including fermentation critical process data analysis, NIR spectral data analysis, and biomarker identification [40, 41]. We used MVDA to analyze the RPKM data to identify “biomarkers” of different DO conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Differentially expressed miRNAs were also observed in biopsies from the sigmoid colon of active UC patients, and quantitative PCR analysis confirmed the presence of two deregulated (both upregulated) miRNAs: miR-21 and miR-155 (92). A recent study comparing colonic mucosa biopsies from active UC or CD patients, quiescent UC or CD patients, and healthy controls, identified miR-20b, miR-99a, miR-203, miR-26b, and miR-98 as being upregulated in active UC compared to quiescent UC, CD, and controls (93). Two miRNAs, miR-125b-1* and let-7e*, were upregulated in quiescent UC compared to active UC, CD, and controls (93).…”
Section: Ii- Biomarker Signaturesmentioning
confidence: 99%
“…A recent study comparing colonic mucosa biopsies from active UC or CD patients, quiescent UC or CD patients, and healthy controls, identified miR-20b, miR-99a, miR-203, miR-26b, and miR-98 as being upregulated in active UC compared to quiescent UC, CD, and controls (93). Two miRNAs, miR-125b-1* and let-7e*, were upregulated in quiescent UC compared to active UC, CD, and controls (93). In the same year (2013), another paper showed that four miRNAs (miR-18a*, miR-629*, let-7b and miR-140-3p) were higher and three miRNAs were lower (miR-422a, miR-885-5p and miR-328) in the mucosa of active CD patients compared to quiescent CD patients, and two miRNAs were higher (miR-650 and miR-548a-3p) and three miRNAs were lower (miR-630, miR-489 and miR-196b) in the mucosa of active UC patients compared to quiescent UC patients (94).…”
Section: Ii- Biomarker Signaturesmentioning
confidence: 99%
“…Furthermore, they found that miR192 participated in the regulation of chemokine production in colonic epithelial cells. Since 2008, some new research in active UC and healthy controls has confirmed the upregulation of miR-21 [25,118] , miR 29a [119] , and miR126 [120] , and identified additional upregulated miRNAs, including miR7, miR29b, miR126*, miR1273p, miR135b, miR223 and miR 3243p [119] , miR31 [119,121] , miR150 [26] , miR155 [118] , miR146a, miR206, and miR424 [121] , and miR 20b and miR125b1* [122] . In contrast, miR1885p, miR215, miR320a, miR346 [119] , and miR200b [123] were downregulated in colon tissues from active UC patients compared with healthy controls.…”
Section: Mirnas In Ucmentioning
confidence: 99%